Phosphorus-doped polyheptylimide and preparation method thereof
By preparing phosphorus doped polycinolide amine in the melting alkaline metal salt environment, maintaining a high crystallinity with a high crystal surface to solve the problem of reduced crystallization of traditional graphite nitride catalyst catalysts, significantly enhanced the light Catalytic performance.
Patent Information
- Application Number
- CN202411718907.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-01-28
AI Technical Summary
Traditional graphite carbon nitride photocatalysts tend to reduce crystallinity during the thermal condensation process, limiting the migration and separation of photogenerated carriers, resulting in insufficient photocatalytic performance.
In the molten alkaline metal salt environment, the phosphorus doped polyxide amine is prepared, and the crystalline surface of the (100) crystal surface is kept through the sufficient mixing and burning treatment of alkaline metal salt and phosphate.
It significantly improves the load migration rate and photocatalytic performance of the photocatalyst, and solves the problem of the high compound rate of photocopy electronics and cave.
Smart Images

Figure CN119371657A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photocatalytic materials, and in particular is a method for preparing phosphorus-doped polyheptazine imide in a molten alkali metal salt environment while maintaining a high crystallinity of a (100) crystal plane. Background Art
[0002] Graphitic carbon nitride (g-C3N4) has become a promising photocatalyst due to its advantages such as visible light absorption, low cost and excellent stability. Graphitic carbon nitride obtained by direct thermal polycondensation of nitrogen-containing precursors is a melon-type polymer based on imine-bridged heptazine units (Lotsch, BV et al., Unmasking Melon by a Complementary Approach Employing Electron Diffraction, Solid-State NMR Spectroscopy, and Theoretical Calculations—Structural Characterization of a Carbon Nitride Polymer. Chem. Eur. J. 2007, 13 (17), 4969-4980.). In the melon structure, the photogenerated carriers are highly confined to the heptazine unit. Due to the high exciton binding energy, the photogenerated carriers are difficult to migrate and separate efficiently (Merschjann, C. et al., Photophysics of polymeric carbon nitride: An optical quasimonomer. Phys. Rev. B 2013, 87 (20), 205204-1-205204-8.). The low crystallinity or disordered characteristics also further aggravate the recombination of photogenerated carriers in melon materials, limiting their photocatalytic performance (Wang, X. et al., A metal-free polymeric photocatalyst for hydrogen production from water under visible light. Nat. Mater. 2008, 8 (1), 76-80.). Adding molten salt during the thermal polycondensation process can change the structure of carbon nitride, converting amorphous melon into crystalline carbon nitride, significantly improving the migration and transmission of photogenerated carriers, and obtaining enhanced photocatalytic performance. For example, crystalline poly heptazine imide (PHI) can be obtained by mixing Melon with LiCl / KCl and further heating in an inert atmosphere.Polyheptazine imide has better photogenerated carrier migration behavior and higher hydrogen production activity (Lin, L. et al., Tri-s-triazine-Based Crystalline Graphitic Carbon Nitrides for Highly Efficient Hydrogen Evolution Photocatalysis. ACS Catal. 2016, 6 (6), 3921-3931.). Melamine and NaSCN / LiCl are mixed and heated under N2 for 4 hours. The synthesized narrow-bandgap polyheptazine imide has an ordered-distorted interface, and the efficient interface carrier separation and transfer promote the improvement of photocatalytic performance (Zhang, J. et al., Heptazine-Based Ordered-Distorted Copolymers with Enhanced Visible-Light Absorption for Photocatalytic Hydrogen Production. Chem Sus Chem 2022, 15 (24), 1-8.).
[0003] The electronic structure and catalytic activity of photocatalytic materials can be adjusted by heteroatom doping. Phosphorus (P) is an element with 5 valence electrons. It has been successfully used to modify Melon photocatalysts by providing an electron-rich system with enhanced conductivity and charge transfer properties (Sun, P. et al., Simultaneously tuning electronic reaction pathway and photoactivity of P, O modified cyano-rich carbon nitride enhances the photosynthesis of H2O2." Appl. Catal., B "2024, 342, 1-9.). However, traditional doping methods are easy to reduce or even destroy the crystallinity of Melon, which is not conducive to the full play of the doping effect. At the same time, studies have shown that the photocatalytic activity of polyheptazine imide significantly depends on the high crystallinity of the (100) crystal plane (Zhang, G., et al., In-Plane Charge Transport Dominates the Overall Charge Separation and Photocatalytic Activity in Crystalline Carbon Nitride. ACS Catal. 2022, 12 (8), 4648-4658.). The design obtains phosphorus-doped highly crystalline polyheptazine imide under the action of molten alkali metal salt without reducing the crystallinity of polyheptazine imide (100). It is expected that the advantageous properties of phosphorus doping and polyheptazine imide structure can be synergistically exerted to obtain efficient photocatalytic materials, which has good application prospects. Summary of the invention
[0004] The purpose of the present invention is to provide a method that can achieve phosphorus doping and polyheptazine imide structure formation in a molten alkali metal salt environment while maintaining (100) crystallinity, thereby solving the problems of easy recombination of photogenerated electrons and holes in g-C3N4 and insufficient photocatalytic activity.
[0005] The technical solution of the present invention is:
[0006] The preparation method of phosphorus-doped polyheptazine imide comprises the following steps: fully mixing and grinding carbon nitride, alkali metal salt and phosphate produced by thermal polycondensation of a nitrogen-rich precursor to produce incomplete polycondensation in a mortar, and then placing them in a crucible and calcining them in a muffle furnace in an air atmosphere. Subsequently, the metal salt is removed by grinding, washing and drying to obtain phosphorus-doped polyheptazine imide, and the (100) crystal plane still maintains a high degree of crystallinity, so that the carrier mobility is greatly improved and the photocatalytic performance is enhanced.
[0007] In the method for preparing phosphorus-doped polyheptazinimide, the metal salt is a binary salt or a ternary salt composed of alkali metal halides (lithium chloride, potassium chloride, sodium chloride). The preferred binary salt is potassium chloride and lithium chloride, with a mass ratio of 1.17 to 1.27. The mass ratio of potassium chloride to sodium chloride in the ternary salt is 1:1, and the mass ratio of lithium chloride to potassium chloride is 0.7 to 1.0.
[0008] In the method for preparing phosphorus-doped polyheptazine imide, when synthesizing incompletely polycondensed carbon nitride, the nitrogen-rich precursor is dicyandiamide, melamine or urea, the thermal polycondensation temperature is 450-550° C., the heating rate is 2-10° C. / min, the thermal polycondensation time is 2-4 hours, and the thermal polycondensation atmosphere is air, nitrogen or argon.
[0009] In the method for preparing phosphorus-doped polyheptazinimide, the phosphate is dipotassium hydrogen phosphate with a mass of 0.005-0.015 g. When preparing the phosphorus-doped polyheptazinimide, the incompletely polycondensed carbon nitride needs to be fully mixed and ground with the alkali metal salt and the phosphate.
[0010] In the method for preparing phosphorus-doped polyheptazinimide, the mass ratio of incompletely polycondensed carbon nitride to alkali metal salt is 1:2.5-1:15, and the mass ratio of phosphate addition to incompletely polycondensed carbon nitride is 0.005-0.015.
[0011] The method for preparing phosphorus-doped polyheptazine imide comprises calcining in an air atmosphere, a calcining temperature of 450-550° C., a heating rate of 2-10° C. / min, and a calcining time of 2-4 hours.
[0012] In the method for preparing phosphorus-doped polyheptazine imide, after the calcination reaction is completed, the obtained solid sample is repeatedly washed with deionized water at a temperature of 25 to 90° C. to remove the remaining metal salt, and then dried in an oven at 50 to 90° C.
[0013] The method for preparing phosphorus-doped polyheptazine imide uses alkali metal salts to achieve changes in the crystal structure of incompletely polycondensed carbon nitride, and can maintain the crystallinity of the polyheptazine imide (100) crystal plane after phosphorus is doped, thereby effectively improving the photocatalytic activity.
[0014] The advantages and beneficial effects of the present invention are:
[0015] The preparation method of phosphorus-doped polyheptazinimide provided by the present invention utilizes alkali metal molten salt to achieve the change of the incompletely polycondensed carbon nitride crystal structure, and the in-situ doping of phosphorus will not destroy the crystallinity of the polyheptazinimide (100) crystal plane, thereby solving the problems of low polymerization degree of carbon nitride and high recombination rate of photogenerated electrons and holes. The present invention has abundant material sources, low price, simple process, and is easy to industrialize. The preparation method of phosphorus-doped polyheptazinimide provided by the present invention is expected to synergistically exert the advantageous characteristics of phosphorus doping and polyheptazinimide structure to obtain efficient photocatalytic materials, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 . is the X-ray diffraction pattern of the sample, wherein the horizontal axis 2θ is the diffraction angle (degree), the vertical axis Intensity is the intensity (au), (1) is Melon, (2) is phosphorus-doped Melon, (3) is polyheptazine imide, and (4) is phosphorus-doped polyheptazine imide.
[0017] Figure 2 . are the electrochemical impedance diagrams of the samples, (1) is Melon, (2) is Phosphorus-doped Melon, (3) is Polyheptazineimide, and (4) is Phosphorus-doped Polyheptazineimide.
[0018] Figure 3 . is the hydrogen peroxide generation rate diagram of the samples, (1) is Melon, (2) is phosphorus-doped Melon, (3) is polyheptazine imide, and (4) is phosphorus-doped polyheptazine imide. DETAILED DESCRIPTION
[0019] The present invention is further described in detail below through examples and drawings.
[0020] Example 1
[0021] (1) Commercial melamine was used as raw material, and a melon-structured carbon nitride was obtained by subjecting it to a thermal polycondensation process in an air atmosphere and subsequent grinding and refinement. The raw material mass was 10 g, the heating rate was 5 °C / min, the treatment temperature was 550 °C, and the holding time was 4 h.
[0022] (2) Place 1 g of Melon, 1.35 g of KCl, 1.15 g of LiCl, and 0.01 g of potassium dihydrogen phosphate in a mortar and grind for 20 min to achieve uniform mixing.
[0023] (3) Place the sample collected in (2) into a 100 ml crucible, place it in the center of a muffle furnace, and heat it in an air atmosphere at a heating rate of 5 °C / min. The target temperature of the muffle furnace is set to 550 °C, and the holding time is 2 h. Cool it to room temperature in the furnace.
[0024] (4) The sample collected in (3) was repeatedly washed and precipitated with deionized water at a temperature of 25°C to remove the metal salt in the sample until no white precipitate was produced when the supernatant was titrated with silver nitrate. The collected sample was dried in an oven at 60°C.
[0025] Example 2
[0026] (1) Commercial melamine was used as raw material, and a melon-structured carbon nitride was obtained by subjecting it to a thermal polycondensation process in an air atmosphere and subsequent grinding and refinement. The raw material mass was 10 g, the heating rate was 5 °C / min, the treatment temperature was 550 °C, and the holding time was 4 h.
[0027] (2) Place 1 g of Melon, 1.35 g of KCl, 1.15 g of LiCl, and 0.015 g of potassium dihydrogen phosphate in a mortar and grind for 20 min to achieve uniform mixing.
[0028] (3) Place the sample collected in (2) into a 100 ml crucible, place it in the center of a muffle furnace, and heat it in an air atmosphere at a heating rate of 5 °C / min. The target temperature of the muffle furnace is set to 500 °C, and the holding time is 2 h. Cool it to room temperature with the furnace.
[0029] (4) The sample collected in (3) was repeatedly washed and precipitated with deionized water at a temperature of 100°C to remove the metal salt in the sample until no white precipitate was produced when the supernatant was titrated with silver nitrate. The collected sample was dried in an oven at 80°C.
[0030] Example 3
[0031] (1) Commercial melamine was used as raw material, and a heat polycondensation process was performed on it under a nitrogen atmosphere, and then grinding and refining were performed to obtain carbon nitride with a melon structure. The raw material mass was 5 g, the heating rate was 2 °C / min, the treatment temperature was 550 °C, and the holding time was 4 h.
[0032] (2) Place 1 g of Melon, 5.2 g of KCl, 5.2 g of NaCl, 4.6 g of LiCl, and 0.005 g of potassium dihydrogen phosphate in a mortar and grind for 1 h to achieve uniform mixing.
[0033] (3) Place the sample collected in (2) into a 100 ml crucible, place it in the center of a muffle furnace, and heat it in an air atmosphere at a heating rate of 5 °C / min. The target temperature of the muffle furnace is set to 550 °C, and the holding time is 2 h. Cool it to room temperature in the furnace.
[0034] (4) The sample collected in (3) was repeatedly washed and precipitated with deionized water at a temperature of 80°C to remove the metal salt in the sample until no white precipitate was produced when the supernatant was titrated with silver nitrate. The collected sample was dried in an oven at 80°C.
[0035] Structural characterization:
[0036] Figure 1 , 2 The complex shown in 3 is a characterization of the complex obtained in Example 1. Figure 1 (1) is an amorphous carbon nitride Melon obtained by polycondensation of nitrogen-rich precursor melamine. A diffraction peak representing the (002) crystal plane of disordered interlayer stacking appears at 27°, and a weaker diffraction peak appears near 13°, representing the (100) crystal plane of the in-plane structure. (2) is phosphorus-doped Melon, and it can be found that its (100) crystal plane has been reduced. (3) is a sample treated with LiCl / KCl molten salt, and the diffraction peak belonging to the (002) crystal plane shifts to a large angle. At the same time, a new diffraction peak appears at around 8°, belonging to the (100) crystal plane of the in-plane ordered structure of the heptazine structure, indicating the formation of a highly crystalline polyheptazine imide structure. (4) is phosphorus-doped polyheptazine imide, and no obvious change is seen in the (100) crystal plane relative to polyheptazine imide, indicating that the liquid environment provided by the molten alkali metal salt enables phosphorus-doped polyheptazine imide to maintain the structural characteristics of polyheptazine imide while maintaining good crystallinity on the (100) crystal plane.
[0037] Figure 2 is the electrochemical impedance spectrum of the composite. The test curve circle radius of phosphorus-doped polyheptazine imide is the smallest, indicating that phosphorus-doped polyheptazine imide has better interfacial charge transfer ability and is more conducive to migrating photogenerated carriers to the catalyst surface, thereby causing redox reactions at the interface.
[0038] Photocatalytic synthesis of H2O2 test
[0039] 10 mg of catalyst was dispersed in 50 mL of aqueous solution containing 10 vol% sacrificial agent isopropyl alcohol (IPA) by ultrasound. The obtained suspension was stirred in the dark for 30 minutes for dark adsorption. The reaction test was carried out under irradiation of a 300 W Xe xenon lamp filtered with a cutoff filter (λ ≥ 420 nm). During the photocatalytic reaction, 4 mL of the suspension was collected at intervals of 10 minutes and filtered through a 0.22 micron microporous filter before measurement to remove excess photocatalyst. The concentration of H2O2 was analyzed by standard iodine titration. That is, 1 mL of the reaction solution was added to a mixed solution of 1 mL 0.1 M potassium hydrogen phthalate (C8H5KO4) solution and 1 mL 0.4 M KI solution and reacted for 30 minutes. Under acidic conditions (H2O2 + 3I - +2H+ →I3 - +2H2O), H2O2 molecules and iodide anions (I - ) reacts to form triiodide anion (I3 - ), which has strong absorption at 350nm. Based on the absorbance at 350nm, the UV-visible spectroscopy was used to measure the 3- The amount of H2O2 produced in the reaction can be estimated from this. Figure 3 For the comparison of the photocatalytic hydrogen peroxide rates of the samples, it can be seen that the H2O2 performance of phosphorus-doped polyheptazinimide is 1.47 times that of polyheptazinimide.
[0040] The results of the embodiment show that a highly efficient phosphorus-doped polyheptazine imide photocatalyst is synthesized by simple thermal polymerization. The present invention utilizes molten alkali metal salts to provide an inert liquid environment to improve the carbon nitride polycondensation process to synthesize polyheptazine imide. Phosphorus doping allows for more efficient separation of photogenerated electrons and holes in polyheptazine imide; the liquid mass transfer environment provided by the alkali metal salt allows the sample to maintain a high degree of crystallinity of the polyheptazine imide (100) crystal plane when doped with phosphorus, and the photocatalytic performance is effectively improved, indicating that this synthesis strategy has broad advantages in designing and synthesizing photocatalysts with good performance. The ordered structure and optimized electronic properties of the prepared phosphorus-doped polyheptazine imide are the reasons for its excellent photocatalytic performance. This study provides a new idea for the preparation of carbon nitride with an ordered structure, adjustable atomic composition, and optimized performance.
Claims
1. A method for preparing phosphorus-doped polyheptazine imide, characterized in that: The incompletely polycondensed carbon nitride prepared by thermal polymerization of a nitrogen-rich precursor at high temperature is mixed with molten alkali metal salt and phosphate and then calcined in air. The metal salt is then removed by grinding, washing and drying to obtain phosphorus-doped polyheptazine imide.
2. The method for preparing phosphorus-doped polyheptazine imide according to claim 1, characterized in that: The metal salt is a binary or ternary salt composed of an alkali metal halide (lithium chloride, potassium chloride, sodium chloride).
3. The method for preparing phosphorus-doped polyheptazine imide according to claim 2, characterized in that: The preferred binary salts are potassium chloride and lithium chloride, with a mass ratio of 1.17 to 1.27; in the ternary salt, the mass ratio of potassium chloride to sodium chloride is 1:1, and the mass ratio of lithium chloride to potassium chloride is 0.7 to 1.
0.
4. The method for preparing phosphorus-doped polyheptazine imide according to claim 1, 2 or 3, characterized in that: When synthesizing incompletely condensed carbon nitride, the nitrogen-rich precursor is dicyandiamide, melamine or urea, the thermal polycondensation temperature is 450-550°C, the heating rate is 2-10°C / min, the thermal polycondensation time is 2-4h, and the thermal polycondensation atmosphere is air, nitrogen or argon.
5. The method for preparing phosphorus-doped polyheptazine imide according to claim 1, 2 or 3, characterized in that: The phosphate is dipotassium hydrogen phosphate.
6. The method for preparing phosphorus-doped polyheptazine imide according to claim 1, 2 or 3, characterized in that: The incompletely polycondensed carbon nitride produced by thermal polymerization of the nitrogen-rich precursor needs to be fully ground and mixed with the alkali metal salt and phosphate.
7. The method for preparing phosphorus-doped polyheptazine imide according to claim 1, 2 or 3, characterized in that: The mass ratio of the incompletely polycondensed carbon nitride to the alkali metal salt is 1:2.5 to 1:15; the mass ratio of the added amount of phosphate to the incompletely polycondensed carbon nitride is 0.005 to 0.
015.
8. The method for preparing phosphorus-doped polyheptazine imide according to claim 1, 2 or 3, characterized in that: The calcination is carried out in an air atmosphere at a temperature of 450 to 550° C., a heating rate of 2 to 10° C. / min, and a calcination time of 2 to 4 hours.
9. The method for preparing phosphorus-doped polyheptazine imide according to claim 1, 2 or 3, characterized in that: After the calcination reaction is completed, the obtained solid sample is repeatedly washed with deionized water at a temperature of 25 to 90° C. to remove the remaining metal salt, and then dried in an oven at 50 to 90° C.
10. Phosphorus-doped polyheptazine imide, characterized in that It is prepared by the preparation method described in any one of claims 1 to 9.